2006
DOI: 10.1136/jcp.2005.032151
|View full text |Cite
|
Sign up to set email alerts
|

Distinction between hereditary and sporadic breast cancer on the basis of clinicopathological data

Abstract: Breast carcinomas can be classified with a high level of certainty as sporadic or related to BRCA1 germline mutations by using a decision tree with age, Ki67 and EGFR. This can be clinically useful in mutation analysis in families with a borderline risk of hereditary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 28 publications
5
58
0
1
Order By: Relevance
“…They often concern well demarcated medullary and poorly differentiated ductal cancers with conspicuous lymphocytoplasmic infiltrates [9,10] that are of high-grade [11] and show high proliferation [12]. In addition, they do not express estrogen (ER), progesterone (PR) or HER-2/neu receptors [13], often lack p27 Kip1 [14], but do accumulate p53 [15], and overexpress cyclin E [16], cytokeratins (CK) 5/6 and 14 [17,18], and EGFR [19][20][21]. These observations point to a carcinogenetic pathway of BRCA1 related breast cancers different from that in sporadic cancers.…”
Section: Introductionmentioning
confidence: 99%
“…They often concern well demarcated medullary and poorly differentiated ductal cancers with conspicuous lymphocytoplasmic infiltrates [9,10] that are of high-grade [11] and show high proliferation [12]. In addition, they do not express estrogen (ER), progesterone (PR) or HER-2/neu receptors [13], often lack p27 Kip1 [14], but do accumulate p53 [15], and overexpress cyclin E [16], cytokeratins (CK) 5/6 and 14 [17,18], and EGFR [19][20][21]. These observations point to a carcinogenetic pathway of BRCA1 related breast cancers different from that in sporadic cancers.…”
Section: Introductionmentioning
confidence: 99%
“…This gene is responsible for most cases of hereditary breast and ovarian cancer. BRCA1-associated cancers are typically high grade and TN, and share common pathologic features such as positive EGFR immunostaining [67][68][69]; also, Foulkes et al [61] found that the majority of these BRCA1-associated cancers that are ER negative (81%) are more likely to develop at a younger age (before age 45), compared to 62% of cancers in women diagnosed after age 65. Furthermore, the proportion of BRCA1-associated cancers that are of the basal phenotype has been estimated to be 88% and 57% by Foulkes et al [61] and Lakhani et al [67], respectively.…”
Section: Definition and Risk Factors Of Tnbcmentioning
confidence: 99%
“…This phenotype has high grade, is ER/PR/ HER2 negative, often of typical or atypical medullar histology, and expresses cytokeratin 5/6, cyclin E, and epidermal growth factor receptor (8 -10). Expression of basal keratins cytokeratin 14 and cytokeratin 5/6, together with ER status, seems to be predictive for BRCA1 mutation status compared with sporadic breast tumors (11).In most studies to date, BRCA2-associated tumors have shown a phenotype between the BRCA1-associated and sporadic tumors (4,5,12). cDNA studies, however, identify a distinct expression profile for BRCA2 tumors (13).…”
mentioning
confidence: 99%
“…In most studies to date, BRCA2-associated tumors have shown a phenotype between the BRCA1-associated and sporadic tumors (4,5,12). cDNA studies, however, identify a distinct expression profile for BRCA2 tumors (13).…”
mentioning
confidence: 99%